Exploring the Relationship between Teacher Attitudes towards Technology Integration in the Classroom - Mufida Yasin, Amalia; Sutrisno, Djoko; Fauzia (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Technology integration in education has become a major concern in modern curriculum development. English teachers play an important role in the successful implementation of technology in the classroom, and their attitude towards technology is a key factor influencing how well it is integrated. This study was conducted to explore the relationship between English teachers' attitudes towards technology and the level of technology integration in teaching, focusing on English teachers in 17 schools spread across four districts. The study utilized a mixed method approach involving both qualitative and quantitative data collection. Qualitative data was collected through in-depth interviews with English teachers, while quantitative data was obtained through a questionnaire distributed to all English teachers in the schools. Data analysis was conducted using triangulation techniques to ensure the reliability and validity of the research results. In addition, this study also measured how English teachers' attitudes towards technology relate to the use of technology in daily teaching. The results show that there is a significant relationship between English teachers' attitudes towards technology and the level of technology integration in the classroom. English teachers who have positive attitudes towards technology tend to be more active in integrating technology into their teaching, while English teachers with more skeptical attitudes tend to make less effective use of technology. The study concludes that in order to improve technology integration in teaching, efforts need to be made to change English teachers' negative attitudes towards technology through adequate training and support.